THE IMPLEMENTATION OF ENGLISH CARTOON MOVIE ON STUDENTS’ SPEAKING ABILITY IN MTS NU SUGIO LAMONGAN - Diah Ayu Restuningsih; Mhd Nur; Lusi Setyorini (Edulitics (Education, Literature, and Linguistics) Journal, 2017)
English cartoon movie is always associated with kids, Basically, the cartoon is entertainment for kids, but nowadays the adults are familiar with this term since some cartoon movies are made for the adults. Speaking is one of the four skills that should be mastered by the students. Every student has a different speaking ability, so it is interesting to describe the research about students’ speaking ability. The purpose of the study is 1) to know the implementation of speaking class in the English Course of MTs NU Sugio Lamongan in the academic year at 2013-2014, (2) To know the students speaking ability in the English Course of MTs NU Sugio Lamongan in the academic year at 2013-2014. The study was conducted in English course of MTs NU Sugio Lamongan. The number of the subjects was 20 students. The design of this research is descriptive qualitative. The data were obtained from observation, questionnaire, and interview. The data were analyzed by data reduction, data display and conclusion drawing or verification. The result of the study showed that by using English cartoon movie and the process of teaching-learning speaking, that can give significant improvement to the students’ speaking ability. They are communication games discussion, and role play. About the result of the questionnaire in percentage table, the responses of students to the teaching speaking are good. Most of them like to learn to speak. They said English especially speaking can make them motivated, enthusiastic, and increase their speaking ability. Moreover based on the result of students’ response, they like very much to the teaching of speaking by using cartoon movie in the English course.